Distribution and spatial autocorrelation of HIV self-tests - Juliane Petenuci Vieira; Camila Moraes Garollo Piran; Natan Nascimento de Oliveira; Marcela Demitto Furtado; Rosana Rosseto de Oliveira; Ieda Harumi Higarashi (Universidade Federal do Ceará, 2024)
Objective: to analyze the distribution and spatial autocorrelation of HIV self-testing rates. Methods: this is an ecological study of distributed HIV self-tests. The records were obtained from secondary data from the Medicines Logistics Control System. Moran's autocorrelation coefficient was used for statistical analysis of spatial dependence. Results: 622,822 HIV self-test records made available in Brazil were analyzed, showing positive spatial autocorrelation with a Global Moran's Index of 0.199 (p=0.046) over the period. There has been an increase in HIV self-testing rates over the years, with the highest rates concentrated in the South and North of Brazil, with a higher concentration of distribution in the 25-29 age group. Conclusion: despite the increase in HIV self-testing rates, there are still significant disparities between states, indicating that strategies for HIV self-test distribution and use are needed in the country. Contributions to practice: this work contributes to the improvement of strategies and the (re)formulation of new health policies aimed at expanding the diagnosis of individuals who have HIV and don't know it.